A Mini-Review: Pyridyl-Based Coordination Polymers for Energy Efficient Electrochromic Application - Liu, Shiyou; Zhang, Ping; Fu, Jianjian; Wei, Congyuan; Cai, Guofa (Frontiers in Energy Research, 2021)
Electrochromic devices (ECDs) show a broad application prospects in many important energy efficient optoelectronic fields, such as smart windows, anti-glare rearview mirrors, low-energy displays, and infrared camouflage, etc. However, there are some factors restricting their development, such as low coloration efficiency, slow switching speed and poor cycling stability. Coordination polymer (CP) is a promising active material for fabrication of high-performance ECD because of ultrahigh coloration efficiency, fast switching speed, and excellent cycling stability. In this review, current advances of CP in energy efficient ECDs are comprehensively summarized and evaluated. Specifically, the effects of composition, coordination bonding and microstructure of the bipyridine- and terpyridine-based CP on EC performances are introduced and discussed in detail. Then, the challenges and prospects of this booming field are proposed. At last, the broad application prospects of the CPs based EC materials and the corresponding devices are also demonstrated, which possess numerous revolutionized effects on our daily life. Hopefully, this review would provide useful guidance and further promote progress on the electrochromic and other optoelectronic fields.